SHELFLIFE ANALYSIS OF TORTA DE ARGAO BUTTER CAKE FROM ARGAO, CEBU, PHILIPPINES - Bejagan, Jima S; Villaganas, Adora A; Villaganas, Victor D (Journal of Agriculture and Technology Management, 2015)
Butter cake is a popular baked product serves for snacks and desserts. The study was conducted to determine the shelf life of the traditional butter cake recipe, Torta de Argao. The shelf-life of the product was measured in terms of physico-chemical (pH; percent moisture content, water activity, percent free fatty acid, and peroxide value); microbiological, expressed as TPC ( coliform; E. coli, Salmonellasp.,yeast and molds); and sensory evaluation ( color, odor, texture, sweetness and flavor). The product samples of Torta de Argao were submitted to the laboratory for its analysis using the various parameters. Results of the study showed that Torta de Argao Butter Cake has satisfied the prescribed FDA standards in terms of microbial limits. Analysis of the physico-chemical attributes have proven that the product possessed the satisfactory product quality. On sensory evaluation, the product showed that it is acceptable in all the quality attributes considered. Under room temperature storage condition, the product can last for only three days which is its limit of acceptable period.